FRI0522 The association between occupational-related mechanical stress and radiographic damage in psoriatic arthritis. (15th June 2017) - Zhou, W; Cook, R; Chandran, V; Gladman, DD; Eder, L
Abstract : Background: Mechanical stress is thought to play a role in the development of psoriatic arthritis (PsA). Objectives: To determine the association between occupational-related mechanical factors and the severity of radiographic peripheral and axial joint damage in patients with PsA. Methods: A retrospective cohort study was conducted in patients with longstanding PsA (>10 years duration). Patients were asked to report all paid employment since the age of 18. The key predictor variables included various occupational-related mechanical exposures. For each job, the Occupational Information Network (O*NET) was used to rate the level of exposure to 11 workers abilities and 16 occupational exposures. The outcomes of interest were the extent of radiographic damage in the peripheral and axial joints, as measured by the modified Steinbrocker score (mSS), and the modified Stokes Ankylosing Spondylitis Spine Score (mSASSS). The association between the predictor and outcome variables was assessed by linear multivariable regression models after adjusting for age, sex, PsA duration and lifestyle habits. Results: 307 eligible patients were analyzed. Univariate analysis identified severeal occupational factors associated with radiographic damage (Table 1 –2). In the multivariable regression analysis prolonged repetitive hand movements was associated with a higher peripheral joint damage score (by mSS, adjusted β=29.5, 95% CI 8.2, 50.8, p=0.007, Table 1 ), while the association between prolonged time spent sitting and lower mSS was of borderline significance (p=0.085, Table 1 ). Additionally, occupations that required higher finger dexterity were associated with higher mSS (adjusted β=5.4, 95% CI 1.6, 9.2, p=0.005, Table 2 ). Regarding axial damage, occupations that involved prolonged walking/running were associated with a higher mSASSS score (adjusted β=4.4, 95% CI 0.1, 8.7, p=0.04). PsA duration was independently associated with both peripheral and axial joint damage (p<0.001). Conclusions: High level of occupation-related mechanical stress is associated with increased radiographic peripheral joint damage. These findings support the potential role of micro-trauma in the pathogenesis of PsA. Disclosure of Interest: None declared